Light-Activatable Transfection System Using Hybrid Vectors Composed of Thermosensitive Dendron Lipids and Gold Nanorods - Takuya Hashimoto; Tomoya Hirata; Eiji Yuba; Atsushi Harada; Kenji Kono (MDPI AG, 2020)
Background: Gene delivery to target cells is crucially important to establish gene therapy and regenerative medicine. Although various virus-based and synthetic molecule-based gene vectors have been developed to date, selective transfection in a site or a cell level is still challenging. For this study, both light-responsive and temperature-responsive synthetic gene vectors were designed for spatiotemporal control of a transfection system. Methods: 11-Mercaptoundecanoic acid-coated gold nanorods were mixed with polyamidoamine dendron-bearing lipids of two types having amino-terminus or ethoxydiethylene glycol-terminus to obtain hybrid vectors. Hybrid vectors were mixed further with pDNA. Then we investigated their physicochemical properties and transfection efficacy with or without near infrared laser irradiation. Results: Hybrid vectors formed complexes with pDNA and exhibited enhanced photothermal property under near infrared laser irradiation compared with parent gold nanorods. Transfection efficacy of complexes was promoted considerably by brief laser irradiation soon after complex application to the cells. Analysis of intracellular distribution revealed that laser irradiation promoted the adsorption of complexes to the cells and cytosolic release of pDNA, which is derived from the change in surface hydrophobicity of complexes through dehydration of temperature-responsive groups. Conclusions: Hybrid vector is promising as a light-activatable transfection system.